Utilization of Virtual Reality as a Sustainable Tourism Promotion Strategy Based on Information Technology in Banten Province - Permana, Basuki Rakhim Setya; Kenedi, Kenedi; Huda, Miftahul (JINAV: Journal of Information and Visualization, 2024)
The rapid development of technology has introduced Virtual Reality (VR) as a new approach to promoting sustainable tourism. This research focuses on the utilization of VR as an innovative strategy for tourism promotion in Banten Province, Indonesia, particularly in key tourist destinations such as Anyer Beach, Tanjung Lesung Beach, Umang Island, and the Great Mosque of Banten. By leveraging VR, tourists can experience a more immersive and interactive preview of these locations, fostering greater interest in visiting and supporting sustainable tourism practices. The research was conducted using surveys, gathering responses from 1,000 participants. The findings indicate that VR significantly enhances tourists' experience by offering detailed visualizations, increasing awareness of environmental sustainability, and encouraging eco-friendly travel behavior. This study demonstrates that VR can be a powerful tool in promoting sustainable tourism, offering both educational and entertainment value, while contributing to the preservation of local culture and natural resources. The results suggest that the integration of VR in tourism promotion strategies can play a key role in advancing eco-friendly tourism development.